A Metaphorical Expressions on Justin Timberlake’s Songs - Miftakhul Nur Rochma; Virny Melisa Irwandi (Proceedings of The ICECRS, 2020)
The purpose of this article is to analyze the types of metaphors and analyze the meaning in the lyrics of the song "Mirrors" and "Cry Me a River" by Justin Timberlake. The method uses qualitative because the data used contains song lyrics. Analysis of documents used to find data consists of phrases and sentences containing metaphorical expressions. The results of the discussion data showed that there are. There are 3 metaphors used in the two songs. These three are: Active Metaphor, Dead Metaphor and Mimatic Metaphor. This song uses metaphors and other types of meaning to beautify the song and to convey implicit messages in the song. The lyrics found in song lyrics have an important role in creating certain feelings and conveying messages.